MERCOSUR: Objectives and achievements - Sam Laird (World Trade Organization (WTO), 1997)
MERCOSUR is one of the most important examples of renewed world-wide interest in regional trade agreements. It may be seen as a consolidation of unilateral reforms undertaken in conjunction with major macroeconomic adjustments. The paper reviews the objectives of MERCOSUR and assesses its achievements. It concludes that considerable progress has been made to achieving a customs union and even beyond that towards a common (but not EU-style single) market, but there are a number of areas where progress is still to be made.
Keywords: F15; 330; Customs union; MERCOSUR; tariffs; non-tariff measures